Has climate change hijacked the environmental agenda? - Pereira, Cássio Cardoso; Negreiros, Daniel; Barbosa, Milton; Goulart, Fernando Figueiredo; Dias, Rodrigo de Loyola; Melillo, Maria Clara; Camarota, Flávio; Pimenta, Mariana Antunes; Cruz, Marina; Fernandes, Geraldo Wilson (Nature Conservation, 2023)
Since the establishment of the Intergovernmental Panel on Climate Change (IPCC), decision-makers have realised that periodic assessments were needed to closely monitor climate change. Studies on it became widespread and include the science of greenhouse gas emissions, the composition of these gases and the extent to which humans have been responsible for climate change. In this sense, the United Nations summit has made significant progress since the Rio Conference (Eco 92), with the creation of the Conference of the Parties (COPs). However, governments should not solely focus on curbing greenhouse gas emissions into the atmosphere. In a society with broad and deep environmental problems, governments, the private sector and non-governmental organisations’ (NGOs) efforts should include biodiversity conservation in their agenda. Solving a single problem, the climate crisis is honourable and urgently needed, but to constrain our ever-increasing land-use footprints on the planet needs the tackling of another equally challenging problem, the loss of biodiversity. The destruction of ecosystems undermines nature’s ability to regulate greenhouse gas emissions and protect against extreme weather, thus accelerating climate change and increasing our vulnerability to it. Therefore, tackling environmental challenges means more than building electric cars, investing in “clean” energy and imposing fines on those who burn forests. To save the environment, scientists, industry, policy-makers and the wider society urgently need to look at other aspects of ecosystem conservation and restoration in the same way they look at the climate agenda.